Cerebrospinal Fluid Pressure-Related Features in Chronic Headache: A Prospective Study and Potential Diagnostic Implications - Bono, Francesco; Curcio, Maria; Rapisarda, Laura; Vescio, Basilio; Bombardieri, Caterina; Mangialavori, Domenica; Aguglia, Umberto; Quattrone, Aldo (Frontiers in Neurology, 2018)
Objective: To identify the pressure-related features of isolated cerebrospinal fluid hypertension (ICH) in order to differentiate headache sufferers with ICH from those with primary headache disorder. Methods: In this prospective study, patients with refractory chronic headaches and suspected of having cerebrospinal fluid-pressure elevation without papilledema or sixth nerve palsy, together with controls underwent 1-hour lumbar cerebrospinal fluid pressure monitoring via a spinal puncture needle. Results: We recruited 148 consecutive headache patients and 16 controls. Lumbar cerebrospinal fluid pressure monitoring showed high pressure and abnormal pressure pulsations in 93 (63 %) patients with headache: 37 of these patients with the most abnormal pressure parameters (opening pressure above 250 mm H2O, mean pressure 301 mm H2O, mean peak pressure 398 mm H2O, and severe abnormal pressure pulsations) had the most severe headaches and associated symptoms (nocturnal headache, postural headache, transient visual obscuration); 56 patients with the less abnormal pressure parameters (opening pressure between 200 and 250 mm H2O, mean pressure 228 mm H2O, mean peak pressure 316 mm H2O, and abnormal pressure pulsations) had less severe headaches and associated symptoms. Conclusions: Nocturnal and postural headache, and abnormal pressure pulsations are the more common pressure-related features of ICH in patients with chronic headache. Abnormal pressure pulsations may be considered a marker of ICH in chronic headache.